1983
DOI: 10.1063/1.332635
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of low-defect-density silicon on sapphire

Abstract: The structure of (100) silicon on (11̄02) sapphire is discussed for films grown by a special, defect-limiting process. A three-epitaxial-step technique, which utilizes both vapor phase epitaxy and solid phase epitaxy, is employed in the fabrication of low-defect-density films. The effects of different Si+ implantation energies and initial Si film thicknesses on the final structure of the film are investigated in order to optimize the electrical characteristics. The improvement in crystalline quality during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…SOS films were found to be highly defective by numerous transmission electron microscopy (TEM) studies, with the most of defects concentrated near the interface between silicon film and the substrate [11], [12], [13], [14], [15]. The stress in SOS films was characterized by Raman spectroscopy [16], giving the values of 7.0±0.3 kbar at room temperature and 8.7±0.3 kbar at 77 K for films with thickness of 0.6Ͳ0.9 ʅm.…”
Section: Introductionmentioning
confidence: 99%
“…SOS films were found to be highly defective by numerous transmission electron microscopy (TEM) studies, with the most of defects concentrated near the interface between silicon film and the substrate [11], [12], [13], [14], [15]. The stress in SOS films was characterized by Raman spectroscopy [16], giving the values of 7.0±0.3 kbar at room temperature and 8.7±0.3 kbar at 77 K for films with thickness of 0.6Ͳ0.9 ʅm.…”
Section: Introductionmentioning
confidence: 99%
“…They propagate along the four equivalent {111} planes. However, they often annihilate in mid-layer, i.e., terminating in {211} type boundaries for microtwins (7,8) and coalescence of two stacking faults on different planes (7). Bulk defects.…”
mentioning
confidence: 99%
“…It has been reported that the density of dislocations is not noticeably affected by the ion implantation and regrowth anneal (Carey et al 1983). The most important improvement to the films quality is in the reduction in the number of planar defects.…”
Section: Introductionmentioning
confidence: 99%